2022
DOI: 10.3390/su142315770
|View full text |Cite
|
Sign up to set email alerts
|

Building Stronger Brand Evangelism for Sustainable Marketing through Micro-Influencer-Generated Content on Instagram in the Fashion Industry

Abstract: Micro-influencers have become powerful sources of information for consumers in the digital age. Marketers have strategically collaborated with micro-influencers as brand endorsers to generate valuable content, which attract the consumers and encourage them to engage with micro-influencers, leading to brand evangelism. This reflects the sustainable consumer‒brand relationships. In Southeast Asia, Instagram stands out as the preferred choice for fashion influencers for sharing product information and boosting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 115 publications
(248 reference statements)
0
8
0
Order By: Relevance
“…Moreover, the study by Rungruangjit and Charoenpornpanichkul [ 48 ] found that micro-influencer-generated content on Instagram can affect consumer–influencer engagements consisting of three dimensions: consuming (passive participation), contributing, and creating (active participation). This leads to sustainable consumer–brand relationships, including positive brand referral, purchase intention, and oppositional brand referral.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study by Rungruangjit and Charoenpornpanichkul [ 48 ] found that micro-influencer-generated content on Instagram can affect consumer–influencer engagements consisting of three dimensions: consuming (passive participation), contributing, and creating (active participation). This leads to sustainable consumer–brand relationships, including positive brand referral, purchase intention, and oppositional brand referral.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Moreover, social networking fans can efficiently spread positive word of mouth and defend their branded entity [ 42 ]. However, many previous research studies have focused on how customer engagement in online communities affects customer satisfaction, commitment, brand trust [ 43 ], brand affect, word-of-mouth [ 44 ], repurchase intention [ 45 ], and brand loyalty [ 46 , 47 ] but overlooked brand evangelism, which is essential in virtual communities because brand evangelism indicates that customers provide full support to the branded entity and build a deep emotional connection with it [ 48 ]. Continuing strong relationships through community fan pages is the most effective method of brand marketing management [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although marketers can initiate e-WOM conversations directed to targeted customers, not all FGCs will exert the same impact on all consumers, with some content achieving a sizeable response, while other content does not [49]. It has been reported that reliable content, when created by online marketers, produces consumer agreement and increased attention to that content or online celebrities; whereas the absence of this reliability results in a failure to continue to view this content [50]. Therefore, creating accurate content represents an essential component in generating a positive customer response [51].…”
Section: Relationship Between Smc and E-wommentioning
confidence: 99%
“…The previous research in the field of business and management underscores the impact of micro-influencers’ comparative advantages and user perception on followers’ engagement and purchase behavior. Specifically, micro-influencers offer advantages such as the potential for targeted communication and the substantial level of trust they establish with their audience [ 10 ], leading to followers of micro-influencers exhibiting higher engagement levels compared to followers of influencers at higher tiers [ 4 , 11 ]. However, existing research has not explored which characteristics of micro-influencers can reflect competitive advantage, that is, the antecedents of competitive advantage are not yet clear.…”
Section: Introductionmentioning
confidence: 99%